Perceptions of psychosocial and interpersonal factors affecting self-management behaviors among African Americans with diabetes - Deepika Rao; Jodi Meyer; Martha Maurer; Olayinka O. Shiyanbola (Exploratory Research in Clinical and Social Pharmacy, 2021)
Background: African Americans are more likely to be diagnosed with diabetes and have diabetes complications as compared to non-Hispanic Whites, but have lesser medication adherence and poorer self-management behaviors. Interventions to improve self-management behaviors may not be successful if psychosocial and interpersonal factors of African Americans are not addressed. Objective: The study objective was to qualitatively explore perceptions of African Americans with type 2 diabetes (T2DM) regarding self-management behaviors and understand the effect of psychosocial and interpersonal factors on behavior change. Methods: Adults with T2DM who self-identified as African American/Black were selected from a cohort participating in a mixed-methods study in a midwestern state. The data collection and analysis were guided by the Integrated Theory of Behavior Change. Ten semi-structured, 60-min, theory-based interviews were conducted and content analysis was utilized to identify themes. Themes were then categorized based on theoretical domains. Results: The sample was mostly female, an average of 52 years old, and had a high school education or more. Four themes were identified. Two themes were categorized as psychosocial factors: 1) attitude and beliefs regarding diabetes and 2) sociocultural influences on self-management, while two were interpersonal factors: 3) role of family and social support and 4) relationships with healthcare professionals. Themes connected back to the theory and directly affected self-management behaviors. Conclusion: Future research should focus on incorporating these themes when designing interventions that improve T2DM self-management behaviors and outcomes in African Americans. Health care professionals should emphasize individualized and culturally appropriate T2DM education and counseling.